"SELF SPIRITUAL THERAPY” KRISTEN - Sudarmanto, Gunaryo (Misioner, 2022)
Covid-19 Pandemic has created many personal problems among Christians. Christian Counsellor has not able to cover it through onsite and online ministry. Believers have to face their problem by themselves. So that they need to have ability to treat themselves by Self Spiritual Therapy. The purpose of this research is to design theological foundations in relationship with counselling pastoral principles and ESQ. To reach the aim, this research uses Qualitative approach with inductive mind and Phenomenological paradigm. The method that be used is ‘exegetic biblical theology-systematic theology’ through literature study, observation and questionnaire. The result shows that believers have ESQ that supported by Anthropological, Theological, Christological, Pneumathological, Ecclesiological, Biblical dan Eschatological approaches. Man is the image and likeness of God who have spirit, so that they able to make relationship with God. Because of sin the ability has destroyed. Christ restores the image of God through his role as the Great Therapist. The Holy Spirit applies and Christ work. He becomes Pharacletos for believers. The believers is the body of Christ. They have an unseparated relationship with Christ. So that they can tell their problems to Him. By the Biblical foundations and eschatological hope, the believers can use their faith, prayer and word of God to make Self Spiritual Therapy. Church and Christian Counsellor need to know and socialize the principles and practice Self Spiritual Therapy. They can train Counselors and bilievers.